Analisa filem "ayat-ayat cinta 2" menggunakan Padlet dalam pengajaran dan pembelajaran CTU151 / Wan Noor Hazlina Wan Jusoh ... [et al.] - Wan Jusoh, Wan Noor Hazlina; Abd Ghani, Ruhaizah; Mohd Noor, Nor Adila; Awang, Azarudin; Sulaiman, Noor Hasyimah (2019)
"Ayat-Ayat Cinta 2" is an Indonesian film directed by Guntur Soehardjanto, adapted from a novel authored by Habiburrahman El Shirazy. The film portrayed many issues including Islamophobia, social, politic and economic matters of Muslim society. Those are among the issues discussed in the course namely Islamic Thought and Civilization (CTU151). One-way communication, dull and passive learning style are factors that caused the students have less interest in the subject. Using and analyzing interesting film as a mechanisme in teaching and learning (T&L) process would spur the interest of learning the subject. In line with development of information technology Web 2.0, Padlet is used as students' platform to demonstrate the result of film analysis. This research aims to evaluate the level of students' acceptance in their activity by using Padlet in learning CTU151. A pilot study was conducted by distributing questionnaire to 35 respondents. Data were analyzed using SPSS 22 by referring to mean score in order to measure the level of students' acceptance towards the activity. The result shows that most of the students agreed that watching and analysing the "Ayat-ayat Cinta 2" film as well as using Padlet in the T&L process manage to improve the level of acceptance, understanding and interest towards the subject by the mean score, 4.03. This result demonstrates that film analysis with the usage of Padlet is a new approach in the CTU151 T&L process. It provides students experienced new method of learning and gives more impact in understanding contemporary Muslim issues. Simultaneously, this new approach manages to achieve the CTU151 learning objectives and inspire other instructors as well.